2009
DOI: 10.1007/s10096-009-0739-z
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory non-antibiotic helper compound diclofenac: an antibacterial drug target

Abstract: Diclofenac sodium (Dc) was found to possess antibacterial activity against both drug-sensitive and drug-resistant clinical isolates of Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, and Mycobacterium spp., in addition to its potent anti-inflammatory activity. The time-kill curve study indicates that this non-steroidal drug exhibits bactericidal activity against Listeria, E. coli, and M. tuberculosis. The antibacterial activity of Dc comes, in part, from its ability to inhibit the DNA synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 52 publications
0
81
1
3
Order By: Relevance
“…Within our study ketorоlaс and ibuprofen showed no antimicrobial activity against S. mutans (the latter, according to our data, in general, was less sensitive to the inhibitory effects of NSAIDs), but were effective (more pronounced for ibuprofen) against S. pyogenes, which is known to have a high sensitivity to antimicrobial agents of different groups and slowly develop resistance to them. According to the reference sources sodium diclofenac showed antibacterial activity against antibiotic-sensitive and antibiotic-resistant strains of listeria and mycobacteria, explained with impaired DNA synthesis of sensitive flora [2]. Use of 30-50 mg/20 g diclofenac for mice reliably protected them from infection caused by gram-negative Salmonella typhimurium [8]; under conditions of our experiment it had practically no effect on gram-negative flora.…”
Section: оригінальні дослідженняmentioning
confidence: 80%
See 1 more Smart Citation
“…Within our study ketorоlaс and ibuprofen showed no antimicrobial activity against S. mutans (the latter, according to our data, in general, was less sensitive to the inhibitory effects of NSAIDs), but were effective (more pronounced for ibuprofen) against S. pyogenes, which is known to have a high sensitivity to antimicrobial agents of different groups and slowly develop resistance to them. According to the reference sources sodium diclofenac showed antibacterial activity against antibiotic-sensitive and antibiotic-resistant strains of listeria and mycobacteria, explained with impaired DNA synthesis of sensitive flora [2]. Use of 30-50 mg/20 g diclofenac for mice reliably protected them from infection caused by gram-negative Salmonella typhimurium [8]; under conditions of our experiment it had practically no effect on gram-negative flora.…”
Section: оригінальні дослідженняmentioning
confidence: 80%
“…On the one hand, acceleration of progression of soft tissue infections of streptococcal etiology (group A) at the application of certain non-selective (ketorolac, ibuprofen and indomethacin), but not COX-2 selective NSAIDs and reduction of efficiency of etiotropic antibiotic therapy were found [1]. On the other hand, in vitro, sodium diclofenac was detected to show antibacterial activity against antibiotic-sensitive and antibiotic-resistant strains of microorganisms, including mycobacteria, associated by the authors with the violation of the DNA synthesis of sensitive flora [2], in addition, antimycobacterial properties of diclofenac have been confirmed in an experiment in vivo [3]. It is also known, that NSAIDs have direct membranotropic effects, due to which, it seems to us, they can have their own antimicrobial activity, by analogy with membranotropic antibiotics, and also modulate the action of antimicrobial agents (stimulate or weaken) [4].…”
mentioning
confidence: 99%
“…Methodical searching from the mid-1960s, notably by scientists 12,13 gave real evidences to the fact that many eukaryote-directed drugs have antimicrobial, anti-pathogenic and anti-virulence properties. Such pharmaceutical compounds developed as drugs to treat non-infectious diseases but having antimicrobial activities are called non-antibiotics.…”
Section: The Antibiotic and Non-antibiotic Storymentioning
confidence: 99%
“…The above non antibiotics can effectively manage the microbial infections of many viruses, mycoplasma, gram-negative and gram-positive bacteria, mycobacterium, yeasts, protozoa, plasmodia, leishmania, trypanosomes, and helminthes. 9,12,13 Many of these are capable of modifying cellular permeability, inhibiting efflux pumps, synergize with various antibiotics, especially for reversal of antibiotic resistance and thus acting as helper compounds. Prontosil, a sulfonamide group exhibits their additional antimicrobial activity.…”
Section: The Antibiotic and Non-antibiotic Storymentioning
confidence: 99%
“…tanto associados entre si, na forma de extratos ou como óleos essenciais extraídos de espécies vegetais quando associados com antibióticos de alta potência disponíveis no mercado (BUSH et al, 2011;EJIM et al, 2011;MAZUMDAR, 2009;AL-BAYATI, 2008;LEHTINEN, 2007;SAKAGAMI, 2005 CHUNG et al, 2011).…”
Section: Diterpenos Derivados De Esqueleto Abietano Isolados a Partiunclassified